Aplikasi Structural Equation Modelling (SEM) pada Pola Kepemimpinan TNI AL - Adijanto, Nugroho; Judijanto, Judijanto; Feriyanti, Nentin (Rekayasa, 2021)
In the era of globalization which is full of change and competition, an organization must show the best performance in order to survive through managing its resources through the right leadership. One indicator of the success of a leadership pattern is the creation of subordinate job satisfaction. With job satisfaction, a subordinate will be able to bring out his best abilities for the benefit of the organization. However, the existence of discipline enforcement efforts will affect the role of leadership patterns in realizing job satisfaction of subordinates in the organization. The purpose of this study is to identify the effect of leadership patterns on the job satisfaction of subordinates, and to identify this effect with the enforcement of discipline as a moderator. In this study, the types of leadership patterns observed were transformational leadership patterns, transactional leadership patterns, visionary leadership patterns and synergistic leadership patterns. Research data obtained from questionnaires distributed to respondents totaling 209 personnel who meet the requirements, then data processing is carried out using the structural equation modeling (SEM) method. The results of the SEM calculation show that without a moderating variable, discipline enforcement efforts, transformational leadership patterns and synergistic leadership patterns affect the job satisfaction of subordinates. Meanwhile, with efforts to enforce discipline, the transactional leadership pattern variable also has an influence on the job satisfaction of subordinates.